2021
DOI: 10.3389/fphys.2021.742871
|View full text |Cite
|
Sign up to set email alerts
|

RNA Interference Suppression of v-ATPase B and Juvenile Hormone Binding Protein Genes Through Topically Applied dsRNA on Tomato Leaves: Developing Biopesticides to Control the South American Pinworm, Tuta absoluta (Lepidoptera: Gelechiidae)

Abstract: The South American pinworm Tuta absoluta (Meyrick) (Family: Gelechiidae) is one of the most devastating lepidopteran pests in the developing countries of South America, Africa, and Asia. This pest is classified as the most serious threat for tomato production worldwide. In the present study, we analyzed RNAi-mediated control through exogenously applied dsRNA delivery on tomato. The dsRNA treatments were made to target the juvenile hormone binding protein and the v-ATPase B. Both mRNA targets were cloned, valid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 66 publications
0
5
0
3
Order By: Relevance
“…Feeding on transgenic plants expressing dsRNA showed a down-regulation of around 90% in B. tabaci aquaporin (AQP) mRNA level 24 hr post-feeding ( Raza et al., 2016 ). The difference in the level of silencing might be due to the variation in concentration of dsRNA, exposure period, target mRNA copies, delivery method, and the host’s defense mechanism ( Ramkumar et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Feeding on transgenic plants expressing dsRNA showed a down-regulation of around 90% in B. tabaci aquaporin (AQP) mRNA level 24 hr post-feeding ( Raza et al., 2016 ). The difference in the level of silencing might be due to the variation in concentration of dsRNA, exposure period, target mRNA copies, delivery method, and the host’s defense mechanism ( Ramkumar et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, the downregulation of T. palmi mRNA in the present study was relatively lower as compared to other thrips species reported previously. The dsRNA concentration, exposure time, target gene expression, delivery method, thrips species, and the defense mechanism of the host might be the reasons behind the variation in the magnitude of silencing ( Ramkumar et al, 2021 ). Silencing of T. palmi Btk29A and COL3A1 negatively influenced had a detrimental impact on T. palmi fitness.…”
Section: Discussionmentioning
confidence: 99%
“…This lepidopteran, which feeds on mesophyll, was subjected to tests with RNAi of the genes: v-ATPase B (keeps the midgut lumen alkaline by increasing amino acid absorption) and JHBP (essential for development and reproductive maturation). Topical application on the leaf surface resulted in 70% of larval mortality for the two target genes [102]. The Asiatic rice borer (Chilo supressalis) is one of the world's main crop pests.…”
Section: Insect Target Genes For Dsrna Silencingmentioning
confidence: 99%